A influência da cafeína na vectoeletronistagmografia computadorizada - Andrade Neto, José Valmir de (2018)
Caffeine is the most widely consumed psychoactive drug and is present in different concentrations in a wide variety of daily consumed products. Caffeine consumption is thought to have an important relationship with vestibular disorders. Some authors recommend stopping the use of caffeine products 72 hours before the test. Others, on the other hand, recommend stopping 48 or even 24 hrs. Some restrict its use up to the day of testing and others don't make any restrictions at all. Nonetheless, abruptly stopping caffeine consumption may cause withdraw symptoms such as fatigue, nausea, vomiting, attention deficit and headaches. Computerized vectoelectronystagmography (VENG), through objective measurements, allows the precise evaluation of the vestibular system which is responsible for the body's equilibrium. Therefore, this study investigated the effect of caffeine in the vestibular system using VENG before and after the ingestion of caffeine capsules. This study taked place in the division of audio health of São José Hospital in the city of Aracaju, Sergipe. The vestibular test was performed twice in the same patient. In the first test, the patient did not drink coffee 48 hours before the exam; in the second, 300 milligrams of caffeine was given to the subjects and rested for thirty minutes. An anamnesis with specific questions was filled out by the evaluator to verify the presence or absence of hearing-related symptoms and body balance, as well as the use of medications and the occurrence of other diseases that cause dysfunction of these systems, as evaluated by the Visual Analogue Scale (VAS) the perception of the participant's current state before the first and second examinations. At the end of the procedure, it was evaluated, through statistical analysis, whether there were significant changes in the examination performed at cessation and after caffeine ingestion.The data obtained in the study were statistically evaluated to look for significant alterations in VENG testing before and after ingestion of caffeine. The sample consisted of 52 women and 18 men. They reported habitual consumption of caffeine. Headache, fatigue, anxiety and reduced concentration were reported by individuals in the cessation of caffeine, and it’s reflected in mean of the VAS from 3.14 (moderate) to 1.44 (mild), after the intake of caffeine. There was not statistically significant difference between the group that presented and the one who did not complain of dizziness when the relative values of the caloric test, VAS and Symptoms before and after the use of caffeine were evaluated. Analysis of the data revealed that ingestion of caffeine did not significantly influence the results of test of vestibular function. The results revealed that a moderate amount of caffeine does not have a clinically significant effect on the results from caloric test VENG.